Labour Market Integration of International Graduates:Evidence from Finland - Giri, Babita (My University, 2026)
ABSTRACT: The expansion of English taught degree programmes has increased international student enrolment in Finland, yet this growth has not translated into comparable levels of labour market integration. While Human Capital Theory assumes that nationally recognized qualifications facilitate smooth entry into skilled employment, international graduates continue to experience persistent education and employment mismatches. This study aims to examine how international graduates perceive the factors shaping their labour market integration through an integrated theoretical lens. Drawing on a sequential exploratory mixed methods design combining qualitative interviews (n = 11) with a quantitative survey (n = 51), the findings show that, despite holding Finnish de-grees, many graduates experience skill underutilization and downward occupational mobility. From a Social Capital perspective, restricted access to locally valued work experience and professional networks constrains the conversion of human capital into employment, producing an enduring “experience paradox.” Extending Career Construction Theory, the study further reveals that integration is an emotionally intensive process marked by sustained identity work, insecurity, and motivational strain during prolonged job searches. This study advances labour mobility and integration scholarship particularly strategic human re-source management by reconceptualizing labour market integration as a relational, emotional, and processual accomplishment. This thesis contributes to construct sharpening through theorizing Human Capital, Social Capital, and Career Construction perspectives while demonstrating how capital conversion, relational embeddedness, and career sense making jointly shape inter-national graduates’ employment trajectories under institutional constraints.
Keywords: career development; career; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business